If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -12 + -2x + 4 + -13 = 20 Reorder the terms: -12 + 4 + -13 + 3x + -2x = 20 Combine like terms: -12 + 4 = -8 -8 + -13 + 3x + -2x = 20 Combine like terms: -8 + -13 = -21 -21 + 3x + -2x = 20 Combine like terms: 3x + -2x = 1x -21 + 1x = 20 Solving -21 + 1x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 1x = 20 + 21 Combine like terms: -21 + 21 = 0 0 + 1x = 20 + 21 1x = 20 + 21 Combine like terms: 20 + 21 = 41 1x = 41 Divide each side by '1'. x = 41 Simplifying x = 41
| 24x^3-21x^2= | | (3x-12)-2x+(-2)-13=-20 | | -4=8-s | | 2-(y+2)=y | | 46x^3+43x^2+5x= | | 2-(y+2)=ey | | 2x(x+3)=12 | | 3x-12+16=2x+10 | | X+5x=3 | | 5x+17-4x=9+4x-7 | | x+7m=78m^2 | | 346*65=x | | 4x+7x-3x=34+6 | | -10x+(-5)-x=28 | | -10x+5-x=28 | | 34*15=x | | -3y-3=1+2y | | -9x-4=203 | | X^2+94=-2 | | 3px(-4)=6 | | 5y-4=19y+108 | | 3x-12+8x=87 | | 0=3x(x-4)(x-1) | | -x+x+30= | | 0=3x(x-4)(x-1) | | 2x-48=52 | | 2x-48=52 | | x+Bx+25=(x+5) | | 2a+3b-5a= | | 6x-4=44-2x | | 2(x-6)-9=19-6x | | 10+.3x=x-2 |